Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2741/3896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thymectomy on cellular immune function

Abstract: The present study was conducted to evaluate the effect of thymectomy during open heart surgery on immunological function of T lymphocytes in the treatment of children with congenital heart disease (CHD). No significant difference was found in the sjTREC level between pre-thymectomy and post- thymectomy in the non-thymectomy group and the small partial resection group (P>0.05) However, the sjTREC level decreased from the pre-surgical level at 1 month (P<0.01) and 12 months (P<0.01) in the sub-total resection gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 18 publications
(22 reference statements)
0
22
0
Order By: Relevance
“…Results obtained by Cao et al showed that the number of naive, TREC-containing T cells may be associated with the size of the preserved thymus fragment. In the group of patients after partial thymectomy (< 50%), the number of TRECs increased after 3 months from the surgery, and preoperative levels were restored after a year; among the remaining patients (in whom more than half of the thymus was removed) the number of TRECs remained significantly lower than the preoperative values, and this effect persisted in the long term [ 30 ]. Thymectomy was also shown to be associated with a decrease in the TCR repertoire and the number of regulatory nTreg cells as well as an increase in the expression of cytokines such as IL-2, IFN-γ, and IL-4 [ 30 ].…”
Section: The Impact Of Thymectomy On the Immune Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Results obtained by Cao et al showed that the number of naive, TREC-containing T cells may be associated with the size of the preserved thymus fragment. In the group of patients after partial thymectomy (< 50%), the number of TRECs increased after 3 months from the surgery, and preoperative levels were restored after a year; among the remaining patients (in whom more than half of the thymus was removed) the number of TRECs remained significantly lower than the preoperative values, and this effect persisted in the long term [ 30 ]. Thymectomy was also shown to be associated with a decrease in the TCR repertoire and the number of regulatory nTreg cells as well as an increase in the expression of cytokines such as IL-2, IFN-γ, and IL-4 [ 30 ].…”
Section: The Impact Of Thymectomy On the Immune Systemmentioning
confidence: 99%
“…The changes in the pool of immune system cells and the disturbances in cytokine expression indicate that thymectomy has a significant influence on the immune function of peripheral T cells, B cells, and cells responsible for congenital immune response [ 28 , 30 ]. Further clinical consequences of these changes are yet to be established.…”
Section: The Impact Of Thymectomy On the Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…3,5 Up to now, there has been no evidence of a negative effect of thymectomy on T-cell function and acquired immune function. 6,7 On the other hand, cumulative steroid therapy has a potentially negative effect on growth and bone mineralization in children with JMG. 8 Thoracoscopic thymectomy seems to be as effective as an open sternal approach (median transsternal approach) in adults.…”
Section: Introductionmentioning
confidence: 99%